Duration of Treatment in Electroconvulsive Therapy Among Patients Beginning With Acute Course Right Unilateral Brief Pulse Stimuli. Issue 4 (December 2021) - Luccarelli, James; McCoy, Thomas H.; Shannon, Alec P.; Forester, Brent P.; Seiner, Stephen J.; Henry, Michael E.
Abstract : Objectives: Right unilateral brief pulse (RUL-BP) electroconvulsive therapy (ECT) has been adopted as a technique for reducing the cognitive side effects of ECT relative to sine wave or bilateral treatments, but it is unknown how often patients are transitioned to alternative electrode placements. This study analyzes time in first lifetime acute course RUL-BP ECT. Methods: A single-center retrospective chart review was conducted of adult patients receiving a first lifetime course of ECT from 2000 to 2017 beginning with individualized seizure threshold determination using RUL-BP treatment parameters. Results: A total of 1383 patients met study criteria and received a mean number of 9.4 ± 3.1 treatments, of which 7.6 ± 3.3 were using RUL-BP stimuli. Only 37.5% of patients were transitioned from RUL to bilateral treatments. Younger patients and those diagnosed with bipolar disorder were more likely to transition from RUL-BP to bilateral treatments, but the overall number of treatments did not differ based on age or primary diagnosis. Conclusions: Among patients who begin treatment with RUL-BP ECT, more than 60% use exclusively those parameters throughout their acute course. Abstract : Supplemental digital content is available in the text.